Pengaturan Fungsi Camat dalam Pemberdayaan Masyarakat Desa dan Implementasinya dalam Pembangunan Desa di Kecamatan Lamboya Kabupaten Sumba Barat: Tinjauan Peraturan Pemerintah Nomor 17 Tahun 2018 Tentang Kecamatan - Jendriensi Tiara H. Lagu; Josef Mario Monteiro; Ivan Ndun (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to analyze the role of the sub-district head (Camat) in community empowerment and village development in Lamboya District, West Sumba Regency, based on Government Regulation Number 17 of 2018 concerning Sub-Districts. The research employed an empirical juridical method with a qualitative descriptive approach. Data were collected through interviews, observations, and literature studies involving the Camat, village heads, district staff, Village Consultative Body (BPD) members, and community representatives. The findings reveal that the Camat has carried out important functions in coordinating, supervising, and guiding village governance and development programs, as well as facilitating community empowerment activities. These roles contribute to improving development implementation and encouraging community participation at the village level. However, the effectiveness of these functions has not been fully optimized due to several obstacles, including limited infrastructure, inadequate human resources, weak coordination among institutions, and inconsistencies in regulatory implementation. These challenges affect the achievement of development objectives and the sustainability of empowerment programs. Therefore, strengthening technical regulations, enhancing institutional coordination, and improving the capacity of government officials are necessary to optimize the Camat’s role in supporting effective village development and sustainable community empowerment in Lamboya District.